Sub-MICs of Azithromycin Decrease Biofilm Formation of Streptococcus suis and Increase Capsular Polysaccharide Content of S. suis - Yang, Yan-Bei; Chen, Jian-Qing; Zhao, Yu-Lin; Bai, Jing-Wen; Ding, Wen-Ya; Zhou, Yong-Hui; Chen, Xue-Ying; Liu, Di; Li, Yan-Hua (Frontiers in Microbiology, 2016)
S. suis (Streptococcus suis) caused serious disease symptoms in humans and pigs. S. suis is able to form thick biofilms and this increases the difficulty of treatment. After growth with 1/2 MIC of azithromycin, 1/4 MIC of azithromycin, or 1/8 MIC of azithromycin, biofilm formation of S. suis dose-dependently decreased in the present study. Furthermore, scanning electron microscopy analysis revealed the obvious effect of azithromycin against biofilm formation of S. suis. Especially, at two different conditions (1/2 MIC of azithromycin nontreated cells and treated cells), we carried out comparative proteomic analyses of cells by using iTRAQ technology. Finally, the results revealed the existence of 19 proteins of varying amounts. Interestingly, several cell surface proteins (such as ABC superfamily ATP binding cassette transporter (G7SD52), CpsR (K0FG35), Cps1/2H (G8DTL7), CPS16F (E9NQ13), Putative uncharacterized protein (G7SER0), NADP-dependent glyceraldehyde-3-phosphate dehydrogenase (G5L259), Putative uncharacterized protein (G7S2D6), Amino acid permease (B0M0G6) and NsuB (G5L351)) were found to be implicated in biofilm formation. More importantly, we also found that azithromycin affected expression of the genes cps1/2H, cpsR and cps16F. Especially, after growth with 1/2 MIC of azithromycin and 1/4 MIC of azithromycin, the capsular polysaccharide (CP) content of S. suis was significantly higher.